More Than a Personal Decision: A Relational Theory of Quiet Quitting - Samnani, Al‐Karim; Robertson, Kirsten (Human Resource Management, 2025)
ABSTRACT Quiet quitting first exploded in social media and has gained considerable traction in media, practitioner, and scholarly outlets. While much of this attention has been focused on why employees quiet quit, there has been less consideration about how it is perceived by their coworkers. Combining insights from relational climate and social networks scholarship, we develop a novel theory about its potential interpersonal consequences. Our theory elucidates how employee quiet quitting and coworker reactions will differ across market pricing, equality matching, and communal sharing climates. We propose that while harmonious relational climates will facilitate the most support from coworkers, these climates will also trigger the most harmful responses when quiet quitting does not eventually dissipate. We also theorize how the collective monitoring and reporting norms that typically develop within these climates will facilitate sanctions via collective forms of mistreatment, such as social undermining and ostracism. Not only does our theory extend the relevant consequences of quiet quitting to include interpersonal ones, but it also therefore explains how seemingly positive climates can inadvertently enable mistreatment. We outline the contributions of our theory to the growing literature on quiet quitting, suggest directions for future research, and offer implications for human resource management practitioners.